Phantom plague: how tuberculosis shaped history - Krishnan, Vidya (New York: Public Affairs, 2022)
"In Phantom Plague, health reporter Vidya Krishnan traces tuberculosis's social and scientific impacts on society throughout history and then brings us into the future with original reporting on the threat of multidrug-resistant TB and its inherent connections with the novel coronavirus. What emerges is a story of patients, scientists, doctors, pharma executives, and activists all connected by one persistent, deadly disease"--
includes index
Keywords: Tuberculosis--Treatment; Diseases and history; Multidrug-resistant tuberculosis; Diseases and history